Learning evolutionary and virulence patterns of influenza viruses - Tan, Tosy Ying Jie (2019)
Without any warnings, influenzas can strike and take away the precious lives of both humans as well as livestock. They are deadly, uninvited and severe. It still remains as a blur amongst experts on how such viruses can actually result into an epidemic or pandemic.